HAK DAN TANGGUNG JAWAB NOTARIS TERHADAP SURAT KETERANGAN (COVERNOTE) ATAS PENGURUSAN SERTIPIKAT PERUMAHAN - IHDINA NIDA MARBUN (PREMISE LAW JURNAL, 2017)
ABSTRACT Land registration is important because land registration is the beginning of the birth process of the proof of land ownership. In Clause 19 administer the registration of land in the entire territory of the republic of Indonesia under the terms of which are set by government regulation. This research was a descriptive analytical, with normative juridical approach is research which refers to the theories, norms, the principles contained in the legislation applicable as a normative foundation. Descriptive in this reasearch describe the fact that developed in the community about rights responsibilities of notary certificate (covernote) on the maintenance of housing certificates. In addition to issuing written evidence in the form of authentic act as a notary public officials also made a statement that is often referred to as covernote. Covernote is a letter explaining that the process is still running in the management of the deeds unfinished and facilitate the process of completeness of the credit agreement. Keywords: Notary, Covernote (statement letter)